Experiences with the levonorgestrel-releasing intrauterine system in Kenya: qualitative interviews with users and their partners. (4th July 2018) - Nanda, Geeta; Rademacher, Kate; Solomon, Marsden; Mercer, Sarah; Wawire, Jim; Ngahu, Rose
Abstract: Objectives: The levonorgestrel-releasing intrauterine system (LNG-IUS) is an underused contraceptive method in sub-Saharan Africa. A recent market assessment in Kenya found that if a more affordable version of the method were available it may increase demand and uptake of the method. We therefore aimed to examine attitudes and perceptions around the LNG-IUS and experiences of method use, including exploring attributes such as bleeding changes, contraceptive-related amenorrhoea and perceived non-contraceptive benefits. Methods: Qualitative interviews were conducted among 29 women who were current or recent users of the LNG-IUS, and among a subset ( n  = 9) of their husbands/partners. Results: Our findings indicate that women's main reason for choosing the LNG-IUS for contraception was their perception that the method had fewer side effects compared with other contraceptive methods. Women had favourable attitudes towards using the LNG-IUS. Husbands were also very positive about their partner's use of the method. Conclusion: Understanding the motivations and experiences of early adopters of the LNG-IUS can help inform the development of demand creation and communication strategies to influence uptake and continuation of the LNG-IUS both in Kenya and perhaps more broadly. Communication efforts that emphasise the positive attributes of the LNG-IUS could help promote wider use of the method, especially if new, more affordable product(s) become available.